Flexural behaviour of reinforced concrete slabs with ferrocement tension zone cover - Al-Kubaisy, M.A.; Jumaat, Mohd Zamin (Elsevier, 2000)
This paper presents a study of the flexural behaviour of reinforced concrete slabs with ferrocement tension zone cover. The results of tests on 12 simply supported slabs are presented. The effect of the following parameters: percentage of wire mesh reinforcement in the ferrocement cover layer, thickness of the ferrocement layer and the type of connection between the ferrocement layer and the reinforced concrete slab on the ultimate flexural load, first crack load, crack width and spacing, and the load-deflection relationship were examined. The results indicate that the use of ferrocement cover slightly increases the ultimate flexural load and increases in the first crack load. The first crack load increased with the increase in the percentage of mesh reinforcement and the ferrocement layer thickness. Considerable reduction in cracks width and spacing (64-84) was observed for specimens with a ferrocement layer. The presence of a cold joint between the reinforced concrete slab and the ferrocement layer lowered the ultimate flexural load by 34, however, cracks width and spacing were reduced. Specimens cast without structural connection, provided that concrete was cast within 1-1.5 h of casting the ferrocement cover, behaved in a very similar manner to those with structural connection. The deflections at service load and near ultimate load were smaller for specimens with ferrocement layer. The ferrocement layer thickness and the connection type influenced the reduction in deflection.